2020
DOI: 10.1097/inf.0000000000002569
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Postlicensure Observational Studies on Human Papillomavirus Vaccination and Autoimmune and Other Rare Adverse Events

Abstract: Background: Because of the limited number of subjects in prelicensure studies, autoimmune diseases and other rare adverse effects of vaccines may go undetected. Since 2006, millions of human papillomavirus (HPV) vaccine doses have been distributed and a considerable amount of postlicensure safety data has been generated. The objective of this study was to review available HPV postlicensure safety studies and to summarize risk estimates of autoimmune and other rare diseases. Methods: For this systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Several studies have found no association between HPV vaccination and autoimmune diseases, a major concern in vaccine safety studies. 13 14 19 37 Although a recent meta-analysis highlighted no clear association between HPV vaccines and autoimmune diseases, the study also suggested a significant increase in the risk 38 We speculated that this increased risk resulted from the unmasking phenomenon, which can occur when vaccinated groups are compared with unvaccinated groups. 22 Visiting a medical institution for vaccination offers an opportunity to assess symptoms that might not have been assessed…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have found no association between HPV vaccination and autoimmune diseases, a major concern in vaccine safety studies. 13 14 19 37 Although a recent meta-analysis highlighted no clear association between HPV vaccines and autoimmune diseases, the study also suggested a significant increase in the risk 38 We speculated that this increased risk resulted from the unmasking phenomenon, which can occur when vaccinated groups are compared with unvaccinated groups. 22 Visiting a medical institution for vaccination offers an opportunity to assess symptoms that might not have been assessed…”
Section: Discussionmentioning
confidence: 97%
“…The safety of HPV was further demonstrated in a recent review and meta-analysis of post-licensure observational studies. The OR for MS was 0.96 (95% CI, 0.77-1.21), and for all the other CNS demyelinating syndromes it was 1.02 (95% CI, 0.77-1.33) (25).…”
Section: Vaccines and Central Nervous System (Cns) Demyelinating Syndmentioning
confidence: 95%
“…Another meta-analysis which comprised twenty-two studies revealed that DM-1, immune thrombocytopenia purpura and chronic thyroiditis were the most frequently reported after HPV vaccination. However, this study demonstrated the absence of a clear association between HPV vaccines and autoimmune diseases and other rare diseases [ 96 ].…”
Section: Human Papilloma Virus Vaccinesmentioning
confidence: 99%